Comparison Of Western Motivation Theories With Islamic Method - Sakat, Ahamad Asmadi; Mohd Zin, M.Z.; Mahdi, Ahmad Faisal; Mohd Nor, Mohd Roslan; Ahmad, N. Azlina; Nazri, Mohd Arif; Abdul Kadir, Muhd Najib; Zainan Nazri, Nurfarhah; Bhari, Azri (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2012)
This article presents the excellence methodology of al-Targhib and al-Tarhib, according to the Qur'an against the Western motivation theory. The privileges mentioned in the Quran and al-Hadith, as well as practiced by the Companions in delivering the message of God, led by the Messenger's. This effort is the medium to those involved in missionary Islamiyya.